Pengembangan Media Pembelajaran Interaktif Berbasis Virtual Reality (VR) Berbantuan Millealab untuk Meningkatkan Hasil Belajar Siswa pada Materi Usaha dan Energi Kelas XI - Harnisa, Sehli; Risdianto, Eko; Putri, Desy Hanisa; Soraya, Indah (Navigation Physics : Journal of Physics Education, 2024)
This study aims to describe the feasibility of interactive learning media based on virtual reality assisted by millealab on work and energy material, describe student responses to interactive learning media based on virtual reality developed on work and energy material, and describe the improvement of student learning outcomes after using interactive learning media based on virtual reality assisted by millealab on work and energy material. The method used is R&D, with the ADDIE model. The results showed: (1) validation of media feasibility, obtained a score of 35, with a percentage of 97.22%; (2) N-gain obtained a value of 0.73; and (3) assessment of student responses to the media, obtained aspects of media display 86.6%, aspects of media use 87.5%, and aspects of the benefits of 86.6%. In total, the percentage obtained was 86.9%. Based on the results, it can be concluded that the use of virtual reality-based learning media assisted by millealab is very feasible to use for work and energy material, there is an increase in student learning outcomes, and gets very good student responses from students.